2016
DOI: 10.1017/asr.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Re-viewing Studies on Africa, #Black Lives Matter, and Envisioning the Future of African Studies

Abstract: Abstract:This article considers what African Studies needs to look like in order for it to retain its disciplinary relevance for the next generation and in the larger context of the Black Lives movement globally. It asks questions about where we have come from in terms of race consciousness in our discipline and why this issue matters today. It begins by tracing the development of African Studies’ epistemic journey, and follows this with an examination of the recent Black student movements in South Africa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…These critiques come at a time when many institutions, including in the worlds of research and international development, are wrestling with urgent ethical failures around race (Ampofo, 2016;Pailey, 2020) and gender (Brown (ed. ), 2019;Goncharenko, 2021).…”
Section: Global Debatementioning
confidence: 99%
“…These critiques come at a time when many institutions, including in the worlds of research and international development, are wrestling with urgent ethical failures around race (Ampofo, 2016;Pailey, 2020) and gender (Brown (ed. ), 2019;Goncharenko, 2021).…”
Section: Global Debatementioning
confidence: 99%
“…The #BLM hashtag was originally introduced on social media (i.e., Twitter) in 2012 by three Black women, Alicia Garza, Patrisse Cullors, and Opal Tometi, after George Zimmerman, who is Hispanic White, was acquitted for a shooting that caused the death of Trayvon Martin, who was an African American teenager (Ampofo, 2016). This hashtag was the impetus for Black Lives Matter (BLM) protests throughout the United States and on college campuses nationwide (Ampofo, 2016). In 2015, BLM protests spread across over 100 US college campuses attempting to address various issues (Ampofo, 2016).…”
Section: Racismmentioning
confidence: 99%
“…This hashtag was the impetus for Black Lives Matter (BLM) protests throughout the United States and on college campuses nationwide (Ampofo, 2016). In 2015, BLM protests spread across over 100 US college campuses attempting to address various issues (Ampofo, 2016). Ampofo (2016) reported that "issues ranged from demands that hostile environments and racist treatment of Black and other students of color be addressed, to calls that curriculums be decolonized and that links to slavery be acknowledged and corrected" (p. 19).…”
Section: Racismmentioning
confidence: 99%
“…Keynote addresses at its annual meetings and special issues in its journals have assessed the practice of the social sciences and the barriers to higher education reform in Africa (Mkwandawire 1997; Aina 2010). They have denounced extra-judicial killings and human rights abuses in Angola and Chad, or called for “African-centered approaches to African Studies” (Ampofo 2016).…”
Section: The Asa@60: Institutional Stability In a World Of Democraticmentioning
confidence: 99%
“…3.For insights into some of the controversies that have shaped, and continue to shape, the ASA and African Studies, see Zeleza (1997); Greene (1999); Mama (2007); Ogot (2009); Ampofo (2016). …”
Section: Notesmentioning
confidence: 99%